Hyperoxia Exacerbates Postnatal Inflammation-Induced Lung Injury in Neonatal BRP-39 Null Mutant Mice Promoting the M1 Macrophage Phenotype - Mansoor A. Syed; Vineet Bhandari (Mediators of Inflammation)
Rationale. Hyperoxia exposure to developing lungs—critical in the pathogenesis of bronchopulmonary dysplasia—may augment lung inflammation by inhibiting anti-inflammatory mediators in alveolar macrophages. Objective. We sought to determine the O2-induced effects on the polarization of macrophages and the role of anti-inflammatory BRP-39 in macrophage phenotype and neonatal lung injury. Methods. We used RAW264.7, peritoneal, and bone marrow derived macrophages for polarization (M1/M2) studies. For in vivo studies, wild-type (WT) and BRP-39−/− mice received continuous exposure to 21% O2 (control mice) or 100% O2 from postnatal (PN) 1 to PN7 days, along with intranasal lipopolysaccharide (LPS) administered on alternate days (PN2, -4, and -6). Lung histology, bronchoalveolar lavage (BAL) cell counts, BAL protein, and cytokines measurements were performed. Measurements and Main Results. Hyperoxia differentially contributed to macrophage polarization by enhancing LPS induced M1 and inhibiting interleukin-4 induced M2 phenotype. BRP-39 absence led to further enhancement of the hyperoxia and LPS induced M1 phenotype. In addition, BRP-39−/− mice were significantly more sensitive to LPS plus hyperoxia induced lung injury and mortality compared to WT mice. Conclusions. These findings collectively indicate that BRP-39 is involved in repressing the M1 proinflammatory phenotype in hyperoxia, thereby deactivating inflammatory responses in macrophages and preventing neonatal lung injury.